Perlawanan Buruh Terhadap Perusahaan Batu Bara Belanda di Teluk Bayur (1926) - Febi Nilawati; Jamil Jamil; Muhamad Sopyan (History Education Department, Universitas Mulawarman, 2022)
This research was motivated by the establishment of the Steenkolen Maatschappij Parapattan (SMP) company which exploited the natural resources and human resources of the workers which caused a resistance. The purpose of this study is to describe the initial conditions of Teluk Bayur before the resistance in 1926 and to describe the forms of resistance in 1926. The type of research used in this research is historical research using heuristic methods, source criticism, interpretation, and historiography. The results show that prior to the riots, SMP was established in 1912, which was the beginning of the riots that occurred in 1926. Dutch involvement extended to the government. In addition to exploiting coal, contracted workers were also exploited by doing hard labor in coal mines with disproportionate salaries until there was an action against a junior high school company in Teluk Bayur on the night of 6-7 November 1926. Sarekat Islam was considered a forum that initiated resistance so that SI was frozen by the Dutch after the incident.